Design responsivo na arquitetura da informação em múltiplos dispositivos: uma análise do sistema SIGA/UFSCar - Dalmazo, Herisson José (Universidade Federal de São Carlos, 2024)
We live in the era that can be called post-computers, the use of smartphones, tablets and smart TVs has grown exponentially in recent years. This process was intensified during social isolation during the COVID-19 pandemic, with increased adoption of remote work and distance learning. In this scenario, there is a need to ensure that digital information environments are displayed and can be used in any context, that is, regardless of the device. Therefore, one of the strategies to achieve this objective is by applying the Responsive Design approach during the creation and development of these environments. With that said, this work is developed based on the following investigative question: how can the absence of Responsive Design in digital information environments impact information architecture, usability and user experience? With this question, it aims to analyze the attributes of Responsive Design for interaction and usability in the informational architecture of digital informational environments. This is a qualitative-quantitative research with an exploratory objective, conducted through bibliographical research through specialized literature to understand the areas of Information Architecture, Interaction Design, User-Centered Design and Responsive Design; and an analysis of the information architecture and responsiveness of the SIGA/UFSCar system, in accordance with the good practices identified. As a result, it was observed that the analyzed system does not have a responsive approach, making it essential to convert the current environment to a fluid design or create a new environment with a user-centered perspective. Furthermore, it is concluded that there are other responsiveness factors that were not considered in this work, therefore further research is necessary to address all the factors and limitations presented.
Responsive design in multi-device information architecture: an analysis of the SIGA/UFSCar system
Diseño responsivo en arquitectura de información multidispositivo: análisis del sistema SIGA/UFSCar
Keywords: Design responsivo; Arquitetura da informação; Usabilidade; Dispositivos móveis; Responsive design; Information architecture; Usability; Mobile devices; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA